Acute amivantamab-induced myocardial injury in a patient with epidermal growth factor receptor-mutant lung cancer: a first case report - Kaneko, Seiya; Dotsu, Yosuke; Inoue, Tomoaki; Motokawa, Tetsufumi; Yoshimuta, Tsuyoshi; Mori, Mayako; Morikawa, Toru; Honda, Noritaka; Akagi, Kazumasa; Tomono, Hiromi; Matsuo, Midori; Taniguchi, Hirokazu; et al. (Frontiers in Oncology, 2025)
BackgroundAmivantamab, a bispecific antibody against epidermal growth factor receptor and mesenchymal-epithelial transition receptors, has been approved for certain types of non-small cell lung cancer; however, it is known to cause severe adverse events. The management of such adverse events is necessary for maintaining the therapeutic efficacy of amivantamab. The frequency of cardiotoxicity caused by amivantamab is low, despite its association with a high incidence of severe adverse events. Most of the adverse events are cardiovascular events caused by thrombosis. No reports of amivantamab-induced myocardial injury have been published.Case presentationWe present the first case of drug-induced myocardial injury, detected with tachycardia but not associated with any cardiovascular events, immediately after initiating amivantamab. Echocardiography revealed a decrease in left ventricular ejection fraction and global longitudinal strain, while contrast-enhanced cardiac magnetic resonance imaging showed shortened T1 values, leading to a diagnosis of amivantamab-induced myocardial injury. Furthermore, with early detection and therapeutic interventions, we were able to continue treatment with amivantamab without interruption.ConclusionsWhen treating patients with amivantamab, oncologists should screen for cardiac disease-related symptoms, even in the absence of elevated cardiac serum biomarkers. Furthermore, when amivantamab-induced myocardial injury is suspected, a cardiologist should be consulted promptly, as the dysfunction may be reversible.